ANALISIS KELAYAKAN FINANSIAL USAHA ROTI PADA INDUSTRI RUMAH TANGGA ZAHRA BAKERY DI KOTA PALU - Korompot, Siti Maimuna; Rahim, Abdul; Lamusa, Arifuddin (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2024)
This study aimed to evaluate the income and financial feasibility of Zahra Bakery, a home industry located at Jalan Angkasa, Komplek RM Satya Bali, North Birobuli, Palu City. The research was conducted from April to June 2022, involving three purposively selected respondents. The analysis applied includes the assessment of investment criteria such as Net Present Value (NPV), Net Benefit-Cost Ratio (Net B/C Ratio), Internal Rate of Return (IRR), and Payback Period (PP). The bakery's average annual production is 576,000 packages, generating an average revenue of IDR 883,200,000. The average cost incurred was IDR 1,094,400,000, resulting in a profit of IDR 91,169,800 and a net cash inflow of IDR 86,245,423. The financial feasibility analysis indicated a positive NPV of IDR 43,794,126, a Net B/C Ratio of 1.24, an IRR of 25.67%, and a PP of 2 years and 7 months, with the final year's net income amounting to IDR 6,610,158/month. These results conclude that the bread business at Zahra Bakery in Palu City is financially feasible for development and operation.